Morphology and properties of thermoplastic starch blended with biodegradable polyester and filled with halloysite nanoclay. (15th August 2020) - Dang, Khanh Minh; Yoksan, Rangrong; Pollet, Eric; Avérous, Luc
Highlights: Halloysite nanotubes (HNTs) improved performances of thermoplastic starch (TPS)-based blends. HNTs enhanced compatibility between TPS and poly(butylene adipate- co -terephthalate) (PBAT). HNTs improved mechanical and thermal properties of the TPS/PBAT blend. Compatibilizing effect of HNTs was more pronounced for the composites with high proportion of TPS. Abstract: The incorporation of halloysite clay nanotubes (HNTs) into thermoplastic starch/poly(butylene adipate- co -terephthalate) (TPS/PBAT) blends has been investigated with the aim of improving the compatibility and properties of the matrix. TPS/PBAT/HNTs nano-biocomposites with different TPS/PBAT weight fractions and HNTs contents were elaborated using a melt blending process, and their morphology and properties were investigated. The TPS80/PBAT20 and TPS20/PBAT80 blends exhibited dispersed phases of small droplets of PBAT or TPS, respectively, whereas the TPS50/PBAT50 blend presented a more homogeneous structure. Elongation at break of the TPS/PBAT/HNTs biocomposites with 5 wt% of HNTs significantly increased with increasing PBAT proportion, i.e., 6.5 %, 41.3 %, and 351.5 % for the composites based on TPS80/PBAT20, TPS50/PBAT50, and TPS20/PBAT80, respectively. The incorporation of 5 wt% of HNTs improved compatibility and increased Young's modulus of the TPS80/PBAT20, TPS50/PBAT50, and TPS20/PBAT80 blends approx. 350 %, 142 %, and 18 %, respectively. These results demonstrate that HNTs are promising nanofillers to improve properties of TPS-based blends.